Жалостью к врагам не страдаем: [роман] / Александр Тамоников - Тамоников А.А. (Спецназ. Воин России, 2010)
Экземпляры: ф.15 (20110512) / Инвентарный номер: 43346 / Цена: 126.00 / Авт.знак: Т 17 / ББК: 84(2Рос=Рус)6